PROBLEMATIKA PENCAPAIAN AKREDITASI PADA MADRASAH ALIYAH DI PROVINSI KEPULAUAN RIAU: PROBLEM OF ACCREDITATION ACHIEVEMENT OF ISLAMIC SENIOR HIGH SCHOOLS (MADRASAH ALIYAH) IN THE PROVINCE OF RIAU ISLANDS - Juju Saepudin (Balai Penelitian dan Pengembangan Agama Jakarta, 2015)
Managing accreditation performance is one of the quality improvement program in the field of education. It is important and strategic effort to provide comprehensible information to the public about the quantitative and qualitative strengths of the madrasa. This paper presents the results of a research on the problem of achieving accreditation of Madrasah Aliyah in the Riau Islands. Using the literature study, observations, interviews and documentations, this study found the weakness of Madrasah Aliyah in Riau Islands in achieving accreditation. It gets average rank on educators, infrastructure and financial standards, mainly for private madrasas. Therefore, the Ministry of Religious Affairs is expected to provide guidance and assistance to support acceleration of accreditation program, and to provide appropriate assistance in relation to the completeness of administrative matters and learning infrastructures. Keywords: Accreditation, Madrasah Aliyah, education, Riau Islands Penyelenggaraan akreditasi merupakan salah satu program peningkatan mutu di bidang pendidikan. Keberadaannya tidak hanya penting, tetapi juga strategis untuk memberikan informasi yang komprehensif kepada masyarakat mengenai kekuatan madrasah, baik secara kuantitatif maupun kualitatif. Tulisan ini menyajikan hasil studi tentang problematika pencapaian akreditasi Madrasah Aliyah di Kepulauan Riau. Pengumpulan data dengan studi pustaka, observasi, wawancara mendalam, dan dokumentasi. Penelitian ini menemukan kelemahan Madrasah Aliyah di Kepulauan Riau dalam pencapaian akreditasi rata-rata berkisar pada standar tenaga pendidik dan tenaga kependidikan, standar sarana dan prasarana serta standar pembiayaan terutama bagi madrasah-madrasah yang statusnya swasta. Oleh sebab itu, Kementerian Agama diharapkan melakukan pembinaan dan pendampingan yang lebih intensif guna mendukung program percepatan akreditasi serta memberikan bantuan secara tepat terkait kelengkapan adminitrasi dan sarana prasarana pembelajaran. Kata Kunci: Akreditasi, Madrasah Aliyah, pendidikan, Kepulauan Riau